Urban social movements: Courses and discourses of emancipatory trials in icoaraci in Belém- PA - Costas, Aelton Dias; Silva, José Augusto Lopes da; Oliveira, Rita Denize de; Santos, Jorge Sales dos (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
The discussions permeate the municipal emancipation of Icoaraci, the current administrative district of Belém, capital of the state of Pará, and gain prominence due to its historical context, where there are several attempts that propel in this same direction, district emancipation. In this sense, the purpose of this work is to try to understand the discourses that promoted these movements, in order to examine the regionalist issue employed in them, together with the icoaraciense indemnity process. For this, a bibliographical and documentary research was carried out, also starting with digital media. There is a strong influence of the power groups present in the region, which end up shaping the regionalist and emancipationist discourse, selling them to the rest of the population.